Diabetes mellitus type 1 in childhood - Valentina A. Peterkova; Marina V. Shestakova; Olga B. Bezlepkina; Dmitry N. Laptev; Tamara L. Kuraeva; Aleksandr Y. Mayorov; Elena V. Titovich; Andrey O. Emelyanov; Galina N. Svetlova; Irina Aleksandrovna Eremina; Irina L. Alimova; Elena B. Bashnina; et al. (Сахарный диабет)
Public organization “Russian Association of Endocrinologists”. Clinical guidlines.